Photodynamic therapy for pulmonary mucoepidermoid carcinoma. (2021) - Kimura, Masakazu; Miyajima, Kuniharu; Ishikawa, Rinako; Yamada, Yuki; Kono, Takafumi; Okunaka, Tetuya; Iwaya, Keiichi; Ikeda, Norihiko
Abstract: Pulmonary mucoepidermoid carcinoma (PMEC) are rare, accounting for 0.1–0.2% of all malignant lung tumors. Furthermore, endobronchial lesions are rare and are more commonly found in the segmental or lobar bronchi. We present, to the best of our knowledge, the first case of successful treatment with photodynamic therapy (PDT) for PMEC. A 77-year-old male presented with cough and hemosputum for 4 months. Chest computed tomography showed a mass in the right intermediate bronchus. Endobronchial biopsy revealed a diagnosis of PMEC. An optimal surgical technique to preserve respiratory function was desirable as most of the tumor emerged from the bronchial glands in the central airways and was of low-grade type. Hence, PDT was performed. Repeat bronchoscopies were performed 5 years after the PDT and showed no evidence of tumor recurrence. PDT is more likely to be effective for low-grade PMECs that are visible on bronchoscopy.